2018
DOI: 10.15698/mic2018.12.659
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of host cell exit by intracellular pathogens

Abstract: Host cell exit is a critical step in the life-cycle of intracellular pathogens, intimately linked to barrier penetration, tissue dissemination, inflammation, and pathogen transmission. Like cell invasion and intracellular survival, host cell exit represents a well-regulated program that has evolved during host-pathogen co-evolution and that relies on the dynamic and intricate interplay between multiple host and microbial factors. Three distinct pathways of host cell exit have been identified that are employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 233 publications
1
70
0
5
Order By: Relevance
“…Intracellular pathogens may induce killing as a strategy to exit from the host cell. Induction of programmed cell death, such as apoptosis, necroptosis or pyroptosis, or the damaging of host cell-derived membranes such as endosomal, vacuolar and plasma membrane have been demonstrated as mechanisms [reviewed in 23]. Reports on the molecular mechanisms underlying S. aureus induced host cell killing are rather inconsistent, which likely arises from the diversity of virulence factors within S. aureus .…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular pathogens may induce killing as a strategy to exit from the host cell. Induction of programmed cell death, such as apoptosis, necroptosis or pyroptosis, or the damaging of host cell-derived membranes such as endosomal, vacuolar and plasma membrane have been demonstrated as mechanisms [reviewed in 23]. Reports on the molecular mechanisms underlying S. aureus induced host cell killing are rather inconsistent, which likely arises from the diversity of virulence factors within S. aureus .…”
Section: Introductionmentioning
confidence: 99%
“…Although in ammation is mainly a defensive response to pathogens with harmful consequences, its downstream effects, such as the metabolic changes or in ux of immune cells, may actually promote the growth of pathogens and the spread of tissues. The de ection of the immune response directed by microbes through speci c signals may further reduce the antibacterial effect and enhance the bene ts of pathogens [(Flieger et al 2018)]. In the pathogen infection, Though the main role of the Tregs is to inhibit damage to tissues and also limit severe in ammation caused by the infection, the accumulation of Tregs also does the opposite, which weaken protecting immune response to pathogens and enhance pathogen persistence [(Stephen-Victor et al 2017a)].…”
Section: Discussionmentioning
confidence: 99%
“…The host cytoskeleton is an obvious target to affect vomocytosis, given its clear role both in maintaining normal cellular structure and in driving the expulsion of several pathogenic bacteria (Flieger, Frischknecht, Hacker, Hornef, & Pradel, 2018). Addition of cytochalasin D, which inhibits actin polymerisation within host macrophages, enhances vomocytosis of C. neoformans (Alvarez & Casadevall, 2006).…”
Section: What Is the Mechanism Of Vomocytosis?mentioning
confidence: 99%
“…The process of vomocytosis requires that internal vesicles release their cargo onto the extracellular milieu. Interestingly, the group showed that the absence of annexin A2, both in vitro and in vivo, results in an enlarged cryptococcal capsule; suggesting that there might be a "sweet spot" in capsule size whereby too small (acapsular strains) or too large a capsule both abrogate vomocytosis.The host cytoskeleton is an obvious target to affect vomocytosis, given its clear role both in maintaining normal cellular structure and in driving the expulsion of several pathogenic bacteria(Flieger, Frischknecht, Hacker, Hornef, & Pradel, 2018). In 2016,Stukes et al showed that annexin A2, a membrane-binding protein involved in bringing membranes together and promoting fusion during several cellular processes including exocytosis of secretory vesicles, affects the occurrence of vomocytosis(Stukes et al, 2016).…”
mentioning
confidence: 99%